Implementasi Kegiatan Outbound Dalam Upaya Pembentukan Perilaku Sosial dan Emosional Anak Usia Dini - Dwi Susari, Hermawati (Jurnal Pendidikan, 2009)
As a social creature, egocentricism nature of any child of kindergarten age needs encouragement and assisstance so as not to hinder the socialization process of the child in the future. In respect of the evidence, this research is attempted to measure the effectiveness of outbond program in establishing the social-emotional skill of kindergarten age children. The finding drawn from observation shows that the development of social-emotional skill of the students of TK Sekolah Alam Bandung is tentatively better than those from coventional ones. The analysis brings about results that social and emotional behaviour of the students of TK Sekolah Alam Bandung develop well by their ability to realize their feelings athough they can not yet controle them. Outbond program is able to develop emotional and social skill of the kindergarten age children. This research then recommend outbond program for kindergarten students.Â Key words : outbound program, social and emotional skill development, kindergarten age children